House as a Hosseiniyeh (Codification of a pattern for Imam Hosseini's houses in Yazd)‎ - Seyed Mohammad Asayesh (صفه)
Establishment of  bereavement ceremony in the form of mourning and lamentations in Hoseiniyehs, ‎Settlement’s, mosques and houses over time is the pride of the people of Yazd's Dar al-Abadah and this love ‎and affection for the Ahl al-Bayt makes the mourning more glorious and magnificence every year. This study ‎describes the characteristics of Yazd's mourning mood in the form of recognizing and introducing the houses of ‎Imam Hosseini in Yazd. Since the people of Yazd provide their homes with mourning ceremonies, this research ‎aims to provide a solution for the continuation of Imam Hosseini's houses by recognizing common features and ‎introducing them in the form of a pattern of spatial relations for these houses. This study been done in Yazd. ‎The research method used in this study is qualitative content analysis in which data collection method has been ‎performed in the field and library or documentary record. In this way, first a brief history of the great and ‎historic martyrdom of Hazrat Sayyid al-Shuhada (as) and after mentioning the historical course of mourning for ‎Imam Hossein (as) to introduce the holy places and mourning centers and express the characteristics of the ‎historical context of Yazd that Imam's houses Hosseini has settled and identifying Imam Hosseini's houses in ‎Yazd and introducing them, the behavior of the mourners and the use of space during the morning in these ‎houses are examined and after identifying the capacity of these houses, which house needs to be able to have ‎an Imam house Hosseini will be introduced. With use of this information for achieve a pattern, the required ‎spaces for these houses are defined and the position and relationships between them are shown in the form of ‎space relations diagram. Finally, the required standards for each of these spaces are summarized.‎